(untitled) - Haight, G. Timothy (Hoboken, N.J., 2007)
This book-one of the very few of its kind-is an invaluable aid to trustees of pension plans, endowments, and trusts who seek to chart and navigate courses for governing and overseeing the investment of the trillions of dollars under their care. It covers many aspects of this essential endeavor, including return measures, fixed income and duration, manager searches, committee meetings, and much more.
Keywords: Investment advisors,Investment advisors; Rating of,Selection and appointment; United States,United States